INTERAKSI SOSIAL BARISTA DAN KONSUMEN DI KOPI SEDUH JENAR, DENPASAR SELATAN - Rahim, Athaur; Punia, I Nengah; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study examines the social interaction between consumers and baristas at Kopi Seduh Jenar, South Denpasar. The type of research used is qualitative descriptive research. The theory used is the symbolic interacionism theory of Herbert Blumer. The results showed that the social interaction between baristas and consumers of Kopi Seduh Jenar was generally an associative social interaction and included cooperative and acculturation mechanisms. Symbols used in social interactions between baristas with consumers at Kopi Seduh Jenar are symbols of languages that manifest in spoken language symbols, gestures and actions, language of images and writings in social media Instagram, as well as Strategic symbols. The interpretation of the symbols on the social interaction of Kopi Seduh Jenar then resulted in social, economic, and educational significance. In the future, more advanced research is required to learn aspects of social interactions and other sociological aspects of coffee shops in Denpasar city. Keywords: Symbolic interactionism, Coffee Shop, Kopi Seduh Jenar